Elemental and Thermo-Chemical Analysis of Oil Palm Fronds for Biomass Energy Conversion - Guangul, F. M. (2011)
Oil palm frond is the most abundant yet untapped biomass waste in Malaysia. This paper investigates the characteristics of raw oil palm fronds and its ash to evaluate its potential utilization as a biomass fuel for gasification process using single throat downdraft gasifier. The morphological nature, elemental content, proximate and ultimate analysis and calorific value were studied. Field emission scanning electron microscopy and x-ray fluorescence were used to investigate the surface morphology, elemental and mineralogical nature of oil palm frond and its ash. The results were compared with other agricultural and forestry biomass wastes. From proximate analysis volatile matter, fixed carbon and ash were found to be 83.5%, 15.2% and 1.3%, respectively on dry basis. From ultimate analysis result values of 44.58%, 4.53%, 0.71% and 0.07% for carbon, hydrogen, nitrogen and sulfur were found respectively on dry basis. Oxygen was determined by difference and found to be 48.81%. The proximate and ultimate analysis results indicate that oil palm frond is better than agricultural wastes and less than most forestry wastes to use as a feedstock in the gasification process in order to get a better quality of syngas. The amount of ash content in OPF was found to be much less than in agricultural wastes and higher than most forestry wastes. From x-ray fluorescence analysis CaO and K2O were found as the major oxides in oil palm fronds and rice husk ash with the amount of 28.46% and 15.71% respectively. The overall results of oil palm fronds were found to be satisfactory to use as a feedstock for the process of gasification.